Potensi Ekstrak Buah Parijoto (Medinilla speciosa blume) sebagai Bahan Aktif Sedian Antioksidan Facial Wash Gel - Vifta, Rissa Laila; Tinasari, Niken Delvin (Generics: Journal of Research in Pharmacy, 2024)
Medinilla speciosa or Parijoto was contains flavonoid which known as a strong antioxidant compound so can be used as an active agent in cosmetic formulation. Antioxidant compounds have ability as free radicals scavenger. Facial wash gel cosmetic formulation are in great demand to clean facial skin to the maximum extent to the pores. The research aims to evaluate the physical stability and antioxidant activity using DPPH method with IC50 parameter. This research is an experimental post design research with maceration as extraction method. Concentration of parijoto fruit gel facial wash formulation were F1 (0.5%), F2 (1%), and F3 (1.5%). Physical stability test for 5 cycles of 10 days which includes organoleptic test, homogeneity test, pH test, viscosity test, foam height test, and antioxidant activity evaluation using DPPH and quercetin as standart. The results of physical stability in the accelerated test for 10 days showed that the preparation was stable during storage (p-value>0.05). Antioxidant activity of Formula 1 (0.5%) obtained IC50 value of 155.32 ppm (very weak), Formula 2 (1%) obtained IC50 value of 137.79 (medium), and Formula 3 (1.5%) obtained IC50 value of 96.17 ppm (strong). The IC50 value of quercetin was obtained at 4.19 ppm (very strong), parijoto fruit extract at 33.13 ppm (very strong), and positive control (market product) at 37.18 ppm (very strong). Keywords : Antioxidant, Facial wash, Flavonoids, Gel, Parijoto, Stability